Structures under Synergetic Effects of Combined Blast and Impact Loads: A State-of-the-Art Review - Solomon Abebe; Tesfaye Alemu Mohammed (Advances in Civil Engineering)
When the effect of combined blast induced shock wave and fragment penetration impact load is sufficiently large enough to induce severe damage in structures compared to individual actions of only-blast and only-impact load, this scenario is called synergetic effect of simultaneous actions. The combined nature of those dual actions aggravates damage and collapses of structures. This paper presented the state-of-the-art review on effect of different parameters, dynamic responses, failure types, and damage mitigation techniques for structures prone to combined actions of blast induced shock wave and fragment impact loads based on findings of experimental, numerical, and analytical research works conducted in previous literature.